Development and Initial Psychometric Validation of an Employability Scale for Indonesian Deaf Students - Elliyatul Munawwarah; Muslihati Muslihati; Im Hambali (Institut Agama Islam Negeri Kerinci, Indonesia, 2026)
This study addressed the assessment gap in special education by developing and validating a contextualized employability scale for deaf students framed within the USEM model (Understanding, Skills, Efficacy Beliefs, and Metacognition). Employing a Research and Development (R&D) design based on the Four-D (4D) model—encompassing the Define, Design, Develop, and Disseminate phases—the instrument underwent expert appraisal by panel members in guidance and counseling, special education, and psychology. Empirical evaluation involved a pilot trial () and field testing with 40 deaf students attending Special Senior High Schools (SMALB). Content validity quantified via Aiken’s V ranged from 0.83 to 1.00 across retained items, demonstrating high expert consensus. Item discrimination analysis using Corrected Item–Total Correlation (CITC) retained 22 of the original 30 items, removing eight items falling below the 0.30 threshold. The refined 22-item scale exhibited superior internal consistency reliability (). These psychometric properties confirm that the scale is a valid and reliable assessment tool tailored to the communication and career development profiles of deaf learners, offering counselors and educators a robust instrument to optimize transition-to-work initiatives and vocational guidance.